Exogenous applied proline may enhance the tolerance of sweet sorghum (Sorghum bicolor (L.) Moench) under water deficit stress - Taş, Timucin; Babacan, Orkun; Işik, Yahya; Genç, Tülay Turgut; Güngör, Hüseyin (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Drought is a major abiotic stress that threatens global food security by reducing crop yield and quality. Foliar application of osmoprotectants such as proline offers a promising means to mitigate drought-induced damage. This study examined the effects of exogenous proline (P0, P200, P400, and P600 mg.L-1), sorghum genotype, and their interaction on morphological, physiological, biochemical, forage quality, and microbial traits under different drought levels (I100, I75, I50, and I25). Proline application increased dry matter by over 100 % under medium to severe deficits and enhanced root dry weight by 90 % at 75 % water reduction. The strongest response occurred in chlorophyll content (SPAD), reflecting improved photosynthetic stability. Exogenous proline reduced leaf drying by 25 % and alleviated drought-related declines in forage quality, as evidenced by improvements in NDF, ADF, and ADL. It also boosted peroxidase activity more than superoxide dismutase and catalase, minimizing hydrogen peroxide (H₂O₂) toxicity and oxidative stress. Even under extreme drought (I25), proline maintained plant vigor and improved water-use efficiency by 25 - 40 % at the seedling stage. Compared with the control, leaf chlorophyll content (SPAD values) decreased by 13.91 %, 24.28 %, and 31.85 % under the I75, I50, and I25 treatments, respectively, suggesting that SPAD measurements at the seedling stage may serve as a practical and cost-effective indicator for identifying drought-tolerant sorghum genotypes.